Effect of the Content of Silicon on the Optical Properties of Al-Si-N Coatings Irradiated with Carbon Ions in the Short-Pulse Implantation Mode; Journal of Surface Investigation. X-ray, Synchrotron and Neutron Techniques; Vol. 16, iss. 5 - Konusov F. V. Fedor Valerievich; Pavlov S. K. Sergey Konstantinovich; Lauk A. L. Aleksandr Lukyanovich; Tarbokov V. A. Vladislav Aleksandrovich; Remnev (Remnyov) G. E. Gennady Efimovich; Gadirov R. M. Ruslan Mukhamedzhanovich (2022, 2022)
Title screen